The Importance of Timing Analysis and Parallelism in the Transmission or Reception of Data - Goncalves de Oliveira, Joel (Recent Advances in Communications and Networking Technology, 2016)
The human mobility need for commercial purposes requires another data transfer. This paper proposes a new data transmission model from three communication entities. The model was presented at the Siemens Award in Brazil. This model evaluates the communication flow, thus establishing a network that will describe the user profile and the recommendation based on each user's profile. This paper will show a data management algorithm. Data analysis is a general problem not only in hardware but also in software. Enabling analysis in both scenarios is the advantage of this algorithm.
Keywords: reputation